Problem Solutions of Increasing Inventory Level for Consignment Material at PT Schneider Electric Batam - Jonathan Edward; Benedictus Rahardjo (Jurnal Titra, 2021)
The raw material used for the production process, 70% comes from outsourcing. This high percentage is the main challenge for PT SEMB to control and ensure raw material is ready when needed. The consignment model has a minimum limit and a maximum limit. The material will be kept at PT SEMB, while not being used these raw materials still owned by the suppliers, and the place to keep this material is not registered as PT SEMB in the system. This means consignment material should have a low inventory level because the ownership will change only when the material is used, but the problem is from January to March 2019 inventory level consignment material has increased. One of the main problems is outdated information for material limits (min-max). This problem solved by making tools that can adjust materials limit (min-max) with the production process and at the same time, it's adjusted with the manpower to do the replenishment process at Lot 15. Improvement also made by changing the person who doing open consignment from leader Lot 15 to warehouse leader Sensor plant. The results for this improvement are decreasing average inventory levels from 362,221 (January-March 2019) to 240,327 (May 2019). Decreasing is approximately 33%